2007
DOI: 10.5006/1.3278417
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Aluminum Alloy 2024 Corrosion by Vanadates: An In Situ Atomic Force Microscopy Scratching Investigation

Abstract: The morphology and kinetics of the localized corrosion of aluminum alloy (AA)2024-T3 (UNS A92024) at the open-circuit potential were investigated by in situ atomic force microscopy (AFM) scratching. The addition of metavanadate to chloride solutions resulted in outstanding corrosion inhibition. Samples exposed to 0.1 M sodium chloride (NaCl) with no inhibitor developed a trench-like attack at the periphery of large Al-Cu-Fe-Mn-(Si) intermetallic phases. The addition of dilute metavanadate markedly reduced the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
44
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(45 citation statements)
references
References 1 publication
0
44
1
Order By: Relevance
“…A similar observation was made by Iannuzzi et al, where metavanadate solutions were observed to suppress S-phase dissolution. 4,30 The chemical maps collected in pH 8 NaVO 3 solutions are possible evidence of localized film formation over the matrix ͑Fig. 11͒.…”
Section: Discussionmentioning
confidence: 99%
“…A similar observation was made by Iannuzzi et al, where metavanadate solutions were observed to suppress S-phase dissolution. 4,30 The chemical maps collected in pH 8 NaVO 3 solutions are possible evidence of localized film formation over the matrix ͑Fig. 11͒.…”
Section: Discussionmentioning
confidence: 99%
“…[5][6][7] Additionally, significant efforts over the last decade have been devoted to understanding corrosion inhibition of AA2024-T3 by vanadates. [8][9][10][11][12] For AA2024-T3, inhibition has been reported to be pH and concentration dependent (speciation dependent) and has been strongly linked to tetrahedrally coordinated vanadates reducing cathodic oxygen reduction kinetics on Cu-containing intermetallic compounds (IMCs) through a surface adsorption mechanism. [11][12][13][14] Other works have shown that vanadates also provide inhibition to Zn-rich Al alloys such as AA7075.…”
mentioning
confidence: 99%
“…16 Frankel et al found that vanadate provided very effective corrosion inhibition on S phase particles even when the protective layer was disturbed with AFM scratching. 22 The FIB data provide additional insight into vanadate interactions with IMCs. Although the FIB image in Fig.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, vanadate has shown good inhibition on aluminum alloys in the form of soluble vanadate, [17][18][19][20][21][22][23][24][25][26] vanadate-based coatings, 27-29 and ion exchange compounds pigment for primers. 30 Iannuzzi et al used polarization and split cell experiments to show that vanadate acted as a cathodic inhibitor on AA2024 by suppressing the oxygen reduction reaction (ORR) by a physically adsorbed vanadate monolayer.…”
mentioning
confidence: 99%
See 1 more Smart Citation